A natureza jurídica da reserva legal e sua aplicabilidade em áreas habitadas por populações tradicionais - FERREIRA, Dauana Santos (Universidade Federal do Pará, 2017)
This paper has studied the legal reservation area, seeking to analyze the juridical nature of this Institute, by means of a Brazilian forest code historic evaluation. This research shows that the legal reservation area is an environmental protection instrument. Its incidence belongs directly on the property right. So, the legal reservation area is obligatory to all private rural properties and possessions in order to fulfill its socio-environmental function. This shifting also verifies in what areas inhabited by traditional populations (extraction reservation, sustainable development reservation, agro-extraction settlement project and Quilombola territory) the legal reservation area will be compulsory.